Optimization of green silver nanoparticles as nanofungicides for management of rice bakanae disease - Quazi Shireen Akhter Jahan; Ziniya Sultana; Md. Asad Ud-Daula; Md. Ashikuzzaman; Md. Shamim Reja; Md. Mahfuzur Rahman; Amina Khaton; Md. Abul Kashem Tang; M. Safiur Rahman; Hossain Md. Faruquee; Seung Ju Lee; A.T.M. Mijanur Rahman (Heliyon, 2024)
Rice bakanae, a devastating seed-borne disease caused by Fusarium species requires a more attractive and eco-friendly management strategy. The optimization of plant-mediated silver nanoparticles (AgNPs) as nanofungicides by targeting Fusarium species may be a rational approach. In this study, Azadirachta indica leaf aqueous extract-based AgNPs (AiLAE-AgNPs) were synthesized through the optimization of three reaction parameters: A. indica leaf amount, plant extract-to-AgNO3 ratio (reactant ratio), and incubation time. The optimized green AgNPs were characterized using ultraviolet–visible light (UV–Vis) spectroscopy, field emission scanning electron microscopy (FESEM) with energy dispersive X-ray (EDX) spectroscopy, transmission electron microscopy (TEM), dynamic light scattering (DLS), and powder X-ray diffraction (XRD) techniques. The optimal conditions for producing spherical, unique, and diminutive-sized AgNPs ranging from 4 to 27 nm, with an average size of 15 nm, were 2 g AiLAE at a 1:19 ratio (extract-to-AgNO3) and incubated for 4 h. Fusarium isolates collected from infected soils and identified as F. fujikuroi (40) and F. proliferatum (58 and 65) by PCR were used for seed infestation. The AgNPs exhibited concentration-dependent mycelial growth inhibition with EC50 values ranging from 2.95 to 5.50 μg/mL. The AgNPs displayed exposure time-dependent seed disinfectant potential (complete CFU reduction in F. fujikuroi (40) and F. proliferatum (58) was observed at a concentration of 17.24 μg/mL). The optimized green AgNPs were non-toxic to germinating seeds, and completely cured bakanae under net-house conditions, suggesting their great nano-fungicidal potency for food security and sustainable agriculture.